Archaeology of Frankish Church Councils, AD 511-768. - Halfond, Gregory I. (Medieval Law and Its Practice Ser., 2009)
Between the reigns of Clovis and Charlemagne (AD 511-768) at least eighty ecclesiastical synods assembled in the Kingdom of the Franks. This book defines the functions and modus operandi of the Frankish church council as an administrative body.